From Sources to Scrolls and Beyond Essays on the Study of the Pentateuch - Carr, David M. (Mohr Siebeck, 2024)
This volume collects essays by David M. Carr which move from a survey of the last half-century of scholarship on Pentateuchal theory to the rationale for and methodologies for such study. Its concluding essays link such research to questions of oral transmission, material history, literary and animal studies.
PublicationDate: 20240528
Keywords: Intertextuality -- Literary Criticism -- Philosophische Theologie -- Isa 61:1 Lxx -- Literary Dependence -- Orality -- material-history -- Zweckentfremdung von Recht -- source-criticism -- MxxxAMPRxxxA (mergers/acquisitions) -- Altes Testament